Strozzate apparizioni. Dell’esperienza inidentica - Pomilio, Tommaso (L'ospite ingrato, 2022)
A wide-ranging retracing of the poetic experience in the passage from the “absolutely modern” to the contemporary and up to the area of the most recent research (placed in parallel, this one, with some of the leading positions of the ‘60s of the previous one): aimed at the definition of that blank, dissipative-generative, de-creating and re-creating, iridescent or entropic, which (from the emergence of the other – not as a person, but as a field of centrifugal tensions) programmatically puts in question the very consistency of a stable identity space, in poetry. That is, of a space that is not that, critical and self-contextual, of an incorporeal pantomime to be played out over the very overwriting of the world, in a glitter of choked, imploded appearances.